ANALYSIS OF DIGITAL TERRESTRIAL TELEVISION TECHNOLOGY ACCEPTANCE USING THE UTAUT2 MODEL - Ariyanto Adi Nugroho; Nanang Susanto (LPPM STMIK Pringsewu, 2023)
Indonesia is currently in a transition period from analog to digital television broadcasting. This paper investigates the factors that influence public acceptance of digital terrestrial television (DTT) technology in Indonesia using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model. A survey of users was conducted to collect data on the factors of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit. The results of the study showed that Age, Habit, Hedonic Motivation, Gender, Facilitation Condition, Salary, Behavioral Intention and Use Behaviour are having an effect to people use Terrestial Television for their activity with fun, enjoyable and use for long term.